BMP2 inhibits TGF-β-induced pancreatic stellate cell activation and extracellular matrix formation - Gao, Xuxia (American Physiological Society, 2013)
Activation of pancreatic stellate cells (PSCs) by transforming growth factor (TGF)-β is the key step in the development of pancreatic fibrosis, a common pathological feature of chronic pancreatitis (CP). Bone morphogenetic proteins (BMPs), members of the TGF-β superfamily, have anti-fibrogenic functions, in contrast to TGF-β, in the kidney, lung, and liver. However, it is not known whether BMPs have an anti-fibrogenic role in the pancreas. The current study was designed to investigate the potential anti-fibrogenic role of BMPs in the pancreas using an in vivo CP model and an in vitro PSC model. CP was induced by repetitive intraperitoneal injections of cerulein in adult Swiss Webster mice. The control mice received saline injections. Compared with the control, cerulein injections induced a time-dependent increase in acinar injury and progression of fibrosis and a steady increase in inflammation. Cerulein injections also induced increases of the extracellular matrix (ECM) protein fibronectin and of α-smooth muscle actin (α-SMA)-positive stellate cells (PSCs). The mice receiving cerulein injections showed increased BMP2 protein levels and phosphorylated Smad1 levels up to 4 wk and then declined at 8 wk to similar levels as the control. In vitro, the isolated mouse and human PSCs were cultured and pretreated with BMP2 followed by TGF-β treatment. BMP2 pretreatment inhibited TGF-β-induced α-SMA, fibronectin, and collagen type Ia expression. Knocking down Smad1 with small-interfering RNA reversed the inhibitory effect of BMP2 on TGF-β-induced α-SMA and fibronectin expression. Thus, BMP2 opposes the fibrogenic function of TGF-β in PSCs through the Smad1 signaling pathway.